Old Media, New Gigs: The Discursive Construction of the Gig Economy in Australian News Media. (June 2023) - Pangrazio, Luci; Bishop, Cameron; Lee, Fiona
This article analyses the representation of the gig economy in three Australian newspapers from 2014 to 2019. 'Gig work' is defined as short term, contract or freelance employment and is seen by many social institutions as the future of work. Drawing on a corpus of 426 articles, Laclau and Mouffe's discourse theory is used to examine the construction of the 'gig economy' in the cultural imaginary. Five key elements emerge, including: demographics of workers; working conditions; workers' rights; resistance and regulation; and change and disruption. Despite multiple competing discourses evident across the newspapers, each constructs the gig economy as an inexorable phase in the evolution of the relationship between capital and the worker. The article critically analyses the construction of the discourse, including the difficulties of regulating gig economy platforms and the narrative of inevitability used to describe changes to work and life brought about by technology.